The FinEs2 Plan as an educational policy. Variations in the period 2013-2019 (Praxis Educativa, 2021)
This article studies the variations in the forms of management of the “Plan de Finalización de los Estudios  Secundarios (FinEs2)” based on the analysis of the narratives of the officials in charge of the government during the period 2013-2019. To do so, we start with a doctoral research conducted in the city of La Plata and,specifically, with the analysis of an empirical corpus built from semi-structured in-depth interviews with officials of this public policy of educational terminality. Finally, we concluded that although the education system presents relative autonomy with respect to the socio-political matrices, it is possible to identify both the continuity of certain definitions on the FinEs2 Plan and other elements that constitute clear ruptures.
Keywords: Plan FinEs2; education; public policy; narratives; official